Voltage-Gated Proton Channels in the Tree of Life - Gustavo Chaves; Christophe Jardin; Christian Derst; Boris Musset (Biomolecules, 2023)
With a single gene encoding HV1 channel, proton channel diversity is particularly low in mammals compared to other members of the superfamily of voltage-gated ion channels. Nonetheless, mammalian HV1 channels are expressed in many different tissues and cell types where they exert various functions. In the first part of this review, we regard novel aspects of the functional expression of HV1 channels in mammals by differentially comparing their involvement in (1) close conjunction with the NADPH oxidase complex responsible for the respiratory burst of phagocytes, and (2) in respiratory burst independent functions such as pH homeostasis or acid extrusion. In the second part, we dissect expression of HV channels within the eukaryotic tree of life, revealing the immense diversity of the channel in other phylae, such as mollusks or dinoflagellates, where several genes encoding HV channels can be found within a single species. In the last part, a comprehensive overview of the biophysical properties of a set of twenty different HV channels characterized electrophysiologically, from Mammalia to unicellular protists, is given.